Characterization of Bacillus cereus isolates from local dairy products in Egypt - Mohamed Aman, Ibrahim; Al-Hawary, Ibrahim Ibrahim; Khattab, Heba Mustafa; Eldesoukey, Ibrahim Elsayed (Penerbit Universiti Kebangsaan Malaysia, 2021)
Bacillus cereus is an important, opportunistic, foodborne pathogen found in various dairy products. In this study, the prevalence, physiological characteristics, antimicrobial resistance profile, and enterotoxigenic genes (ces and hblA) of B. cereus were investigated in isolates from Egyptian dairy products. A total of 150 samples, including soft white cheese, milk powder, and ultra-high temperature (UHT) milk (50 of each), were collected from local dairy stores in EL-Gharbia governorate, Egypt from April 2019 to October 2019. Of these, 29 samples were contaminated with B. cereus (an overall prevalence of 19.3%). Based on cultural, morphological, and biochemical characteristics, 48 isolates were detected including 27 (56.25%) from soft white cheese, 9 (18.75%) from milk powder, and 12 (25%) from UHT milk. Antibiotic susceptibility assessment showed that all isolates exhibited high sensitivity to amikacin, doxycyclin, gentamycin, ciprofloxacin, while significant resistance to kanamycin, clindamycin, nalidixic acid, cephalothin, and sulphamethoxazole was also observed. All isolates were examined for the presence of emetic (ces) and diarrheal (hblA) genes using the PCR method; ces was detected in 12 (25%) isolates, hblA in 14 (29.2%) isolates, while 22 (45.8%) isolates did not harbor either gene. These findings indicate the need for the application of adequate preventive measures and personnel hygiene in dairy processing lines to minimize B. cereus load in final products.